Parasitism Efficiency of Encarsia Lutea Masi on Bemisia tabaci (Genn.) and its Interaction with Insecticides Applied on Cotton Crop in New Halfa Agricultural Scheme (Sudan - E. Abdalla, Tag Elsir (المجلة الزراعية; مجلد 3 عدد 1 (2005), 2021)
The study was conducted at the commercial field of New Halfa Agricultural Scheme (NHAS), during 2001/02 and 2002/03 seasons, to determine the parasitism efficiency of Encarsia lutea Masi (Hymenoptera: Aphelinidae) on Bemisia tabaci (Genn.) (Homoptera: Aleyrodidae), and its interaction with the insecticidal treatments carried against the insect pests of cotton. The parasitoid, microscopically determined inside the whitefly nymphs, started to appear in both seasons since early November and increased towards the end of the season. Parasitism showed density dependence with the whitefly adult numbers leaf, In the first season, the highest level of parasitism was 45.4%. average for November was 23.2%, December 40.3% and for the season was 27.5%. In the second season, the highest level of parasitism reached was 48.2%, the average for November was 9.3%, December and the season's average was 27.2%. E. lutea delayed the insecticidal applications against the whiteflies during November in both seasons and kept them low during December so that no insecticidal interference was needed. The parasitoid secured saving of 29% of the sprays that should have been applied in the first season, and 50% in the second season. This was roughly estimated as three million US dollars directly saved resources in both seasons, besides the indirect benefit of improving the grade of the cotton fibre, due to reduction of the immature stages of the whiteflies. Four insecticide mixtures, of the 12 applied in the two seasons, reduced parasitism by 3%-45%. The rest did not interfere with the incidence of parasitism.